2017
DOI: 10.1002/cncr.30759
|View full text |Cite
|
Sign up to set email alerts
|

Supporting cancer family caregivers: How can frontline oncology clinicians help?

Abstract: There is growing recognition of the demands placed on unpaid family members of patients with cancer, the need to support family caregivers, and the barriers that exist to meeting their needs. This commentary offers several messages that oncology providers can deliver to family caregivers to support them and empower them to seek the services they need.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 15 publications
1
4
0
Order By: Relevance
“…Our study found that caregivers experience being in an unpredictable and unfamiliar territory with difficulties processing complex information. Similar to our findings, previous studies have found that caregivers find it challenging to manage complex patient care needs, and the support from healthcare professionals is valuable 24,42 . These findings stress the importance of healthcare professionals acknowledging how the caregiver is affected and consider caregivers’ life situations and resources 27 .…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Our study found that caregivers experience being in an unpredictable and unfamiliar territory with difficulties processing complex information. Similar to our findings, previous studies have found that caregivers find it challenging to manage complex patient care needs, and the support from healthcare professionals is valuable 24,42 . These findings stress the importance of healthcare professionals acknowledging how the caregiver is affected and consider caregivers’ life situations and resources 27 .…”
Section: Discussionsupporting
confidence: 90%
“…Similar to our findings, previous studies have found that caregivers find it challenging to manage complex patient care needs, and the support from healthcare professionals is valuable. 24,42 These findings stress the importance of healthcare professionals acknowledging how the caregiver is affected and consider caregivers' life situations and resources. 27 It also reflects a need for more individualized information and guidance at the beginning of the trajectory and subsequently as patient needs might change according to the patients and caregivers' needs and resources.…”
Section: Discussionmentioning
confidence: 95%
“…Hence, it appears that caregivers might benefit from a supportive network, made up not only of family members or friends but also resources from within the community. It may be useful to give caregivers a list of available resources about the various organisations involved in cancer care when their partner is first diagnosed, even if they are not particularly distressed at this time, so that they have accurate information and support (Porter & Dionne‐Odom, ). In addition, in the current study low levels of physical and sports activity also predicted anxiety.…”
Section: Discussionmentioning
confidence: 99%
“…give caregivers a list of available resources about the various organisations involved in cancer care when their partner is first diagnosed, even if they are not particularly distressed at this time, so that they have accurate information and support (Porter & Dionne-Odom, 2017). In addition, in the current study low levels of physical and sports activity also predicted anxiety.…”
Section: Discussionmentioning
confidence: 99%
“…Beyond concerns about caregiving responsibilities, caregivers in our study appreciated the opportunity to identify, share, and address their needs related to their own well-being, as well as that of their family member with cancer. In lieu of formal assessment, practitioners can greatly benefit caregivers by acknowledging that caregiving can be challenging, reinforcing that caring for themselves is essential, and providing a list with key informational and supportive care resources available to them (Porter & Dionne‐Odom, 2017). Implementing extant validated screening procedures such as CancerSupportSource-Caregiver, however, would help better ensure all caregivers’ needs are routinely and comprehensively assessed and addressed.…”
Section: Discussionmentioning
confidence: 99%